Revitalizing the Folklore of Bukit Menoreh: Transmitting Cultural Values to Foster Social Awareness in Social Studies Education - Sumpana Sumpana; Saiful Bahri (Indonesian Journal Publisher in cooperation with Indonesian Social Studies Association (APRIPSI), 2026)
Folktales function as important tools for conveying cultural values and shaping social behavior. Yet in modern education, the meaningful messages embedded in traditional narratives, including those from Bukit Menoreh, often receive limited attention in classroom learning. This study explores how Bukit Menoreh folktales can be revitalized as creative Social Studies learning resources to enhance students’ social awareness. Using a qualitative descriptive method with an ethnographic orientation, the research collected data through literature review, interviews with teachers and cultural informants, and content analysis of folktale texts. The analysis involved thematic reduction, organization, and interpretation to identify cultural values relevant to instructional goals. Findings reveal that Bukit Menoreh folktales highlight cooperation, solidarity, and social responsibility, which can be integrated through reflective learning activities. Revitalizing these stories encourages empathy and student engagement with surrounding social issues, demonstrating their significant potential as contextual learning resources that help strengthen students’ character.